Gluconeogenesis and effect of nutritional status on TCA cycle activity in the insect Manduca sexta - Thompson, Stewart N. (Biochimica et biophysica acta, 1995)
Gluconeogenesis from isotopically substituted (3- 13C)alanine (Ala) was demonstrated in the last larval instar of an insect, Manduca sexta, when maintained on low carbohydrate diets. 13C was incorporated into all carbons of the blood sugar trehalose (Tre), but enrichments of C1 and C6, and C2 and C5 were greatest. Relative to the amount of [3- 13C]Ala metabolized, larvae maintained on a low carbohydrate diet supplemented with casein displayed the greatest enrichment of Tre. Very little de novo synthesis of Tre was observed in larvae maintained on a complete-balanced diet containing calorically equivalent amounts of sucrose and casein. Starvation failed to induce gluconeogenesis and 13C was not incorporated into Tre in starved insects. Activity of the TCA cycle contributed approximately 10% of the 13C incorporated into Tre in larvae on low carbohydrate diets, while the TCA cycle contribution in larvae on the complete diet approached 70%. The pattern of 13C enrichment of glucose in larvae on the low carbohydrate diets indicated that cytoplasmic carboxylation, possibly due to ‘malic enzyme’-like activity, contributed significantly to the synthesis of Tre. The pentose phosphate pathway was evidenced in insects on all diets. Glucose labelling ratios indicated a pentose cycling flux of 10 to 20% in insects on the low carbohydrate diets and 50% in larvae on the complete diet. Glutamine together with lesser amounts of glutamate and glutathione were also products of the labelled Ala. The distribution of label in these products under different dietary conditions demonstrated shifts in the relative contribution of pyruvate carboxylase and pyruvate dehydrogenase activities for providing substrate to the TCA cycle. In the expected fashion starved insects and insects on the low carbohydrate diets incorporated a greater proportion of 13C into the TCA cycle via carboxylation while incorporation by the two pathways was similar in insects on the complete diet. The significance of these findings with regard to the regulation of gluconeogenesis in M. sexta and comparison of the present results with those obtained from studies of hepatic gluconeogenesis are discussed.